Stable cyclic performance of nickel oxide–carbon composite anode for lithium-ion batteries - Wang, Xinghui (2014)
Nickel oxide (NiO) directly grown on nickel foam is regarded as a promising lithium ion battery anode material which shows good cyclic and rate performances with a theoretical specific capacity of 718 mAhg−1. In this study, we demonstrated a carbon-incorporated NiO anode (NiO–C) with a capacity per unit area of 2.11 mAhcm−2 and 1.76 mAhcm−2 at 0.2 C and 0.5 C rates, respectively, fabricated by thermal oxidation of carbon coated nickel foam. The specific capacity of our NiO–C composite samples at 0.5 C rate is found to be typically 389.16 mAhg−1, with a stable cyclic performance up to more than 100 cycles. This remarkable performance is apparently superior to the control samples of pure NiO samples. The improved performance is contributed to carbon incorporation which serves as a fluent channel for electrons and a flexible network preventing NiO nanostructures from structural deformation during charge and discharge processes. The advantage of using our approach is the easy preparation of the NiO–C composite using a simple two-step process: chemical vapor deposition of ethanol and annealing in air.